PRODUCTION OF CERTAIN PRO- AND ANTI-INFLAMMATORY CYTOKINES DURING STIMULATION BY LIVE AND INACTIVATED LEPTOSPIRA PATHOGENS IN THE MODEL OF HUMAN WHOLE BLOOD - O. A Petrova; N. A Stoyanova; N. K Tokarevich; N. A Arsentieva; N. E Lyubimova; A. V Semenov; A. Totolyan Areg (Журнал микробиологии, эпидемиологии и иммунобиологии, 2015)
Aim. Study of the ability of clinical isolates of leptospira to cause production of certain pro-and anti-inflammatory cytokines in the model of human whole blood. Materials and methods. Leptospira interrogans strain was taken for the experiment. Cytokine content was determined by a method based on xMAP technology using a standard panel, composed of 9 analytes: TNF-a, MСP-1, IL-8, IL-4, IL-6, IL-10, IL-1Rn, IL-12^70), IFN-y. Results. An optimal concentration of L. interrogans was selected for stimulation of human whole blood - 1x106 leptospirae/ml. For the first time in the model of human whole blood it was determined, that at early stages of incubation IFN-y, IL-12(p70), IL-4 and IL-1Ra are more actively produced; at later stages (6 hour incubation) - IL-8 and TNF-a. Conclusion. A differential pattern of cytokine production stimulation was shown in the model of human whole blood by live and inactivated leptospirae.